(untitled) (International conference on multidisciplinary science, 2023)
The main peculiarity of the microclimate of the wheat biotope is that the number of plants is 400-500 plants per 1 m² area, and if it produces 5 plants on average, 2000-2500 spikes appear, productivity depends on the development of these phases. In addition, winter wheat seeds are sown in September and wintered in the budding phase, from early spring until the crop ripens in 80-90 days, and the crop is harvested in June. Despite these characteristics of wheat, many weeds and pests appear in the field, and it is known that the main part and quality of the harvest will decrease if the controlling measures are not properly organized.